1983
DOI: 10.1007/bf01496660
|View full text |Cite
|
Sign up to set email alerts
|

High amylase content of neoplastic pleural and pericardial effusion probably secondary to amylase producing tumor cells: Report of 2 cases

Abstract: We report two cases of malignant pleural and pericardial effusion respectively secondary to bronchogenic carcinomas. In both effusions, a significant elevation of the Salivary-type-amylase fraction was found, while the corresponding values were normal in serum and urine. Electronmicroscopy of the malignant tumor cells from the pleural effusion showed typical electron-dense granules, suggesting zymogen granules. It is concluded that the high amylase content of the effusions was due to secretion of S-type-isoamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Elevated pleural fluid amylase can be observed in association with pancreatitis, pancreatic pseudocyst with pleural fistula, esophageal rupture, and malignancy [61][62][63][64][65]. Malignancies associated with elevated pleural amylase include carcinomas of the lung, ovary, salivary gland, stomach, and colon [62,63,65].…”
Section: Pleural Fluid Amylasementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated pleural fluid amylase can be observed in association with pancreatitis, pancreatic pseudocyst with pleural fistula, esophageal rupture, and malignancy [61][62][63][64][65]. Malignancies associated with elevated pleural amylase include carcinomas of the lung, ovary, salivary gland, stomach, and colon [62,63,65].…”
Section: Pleural Fluid Amylasementioning
confidence: 99%
“…Malignancies associated with elevated pleural amylase include carcinomas of the lung, ovary, salivary gland, stomach, and colon [62,63,65]. It is interesting to note that esophageal rupture and malignancies of the lung, ovary, and salivary gland are distinguishable from other conditions by the elevation of the salivary isoenzyme of amylase [61,[63][64][65]. This test cannot establish a malignant etiology and should be used in cases where pancreatitis, pseudocyst, or esophageal rupture are suspected.…”
Section: Pleural Fluid Amylasementioning
confidence: 99%
“…2,11,12 Salivary-type amylase is produced in the salivary glands, lungs, and fallopian tubes and may be secreted ectopically by a variety of tumors. [12][13][14][15][16][17] In a prospective study of 200 patients with pleural effusions, Joseph et al 2 performed isoenzyme analysis on 18 of 25 amylase-rich effusions, confirming previous case reports that malignant, infectious, and other nonpancreatic effusions have primarily salivary-type amylase. 2,11,[15][16][17][18] Case reports and animal experiments have demonstrated consistently that pleural effusions from esophageal ruptures contain high levels of salivary-type amylase, 1,19 presumably from the passage of amylaserich saliva through the tear and into the pleural space.…”
Section: Isoenzymesmentioning
confidence: 71%
“…1 When malignant effusions have elevated amylase levels the amylase is usually of the salivary type 2,[11][12][13][15][16][17] and is produced ectopically by the tumor cells. [12][13][14][15][16] It is also possible for amylase to accumulate in the pleural space due to tumor obstruction of the pleural lymphatics. 2 Malignancy is often unsuspected at the time of thoracentesis, and it has been suggested that elevated pleural fluid amylase levels (especially of the salivary type) in the absence of pancreatic disease or esophageal rupture should prompt a search for occult malignancy.…”
Section: Esophageal Rupturementioning
confidence: 99%
“…The anatomical sites of metastasis may be more important than t w o u r mass. Thus, a few lung carcinomas with pleural or pericardial metastases with a significant elevation of amylase in serosal effusions, but a normal serum amylase, have been reported (4,19). Increased amylase activity in tumour tissue may also be due to a severe infiltration of neutrophils (27).…”
Section: Discussionmentioning
confidence: 99%